Photocurrent generation by helical peptide monolayers integrating light harvesting and charge‐transport functions1. Issue 1 (19th January 2013) - Moritoh, Ryosuke; Morita, Tomoyuki; Kimura, Shunsaku; Maran, Flavio; Toniolo, Claudio
Abstract In this study, we construct photoenergy‐conversion systems with chromophores located with molecular precision to facilitate efficient light harvesting and charge transport. 310‐Helical peptides carrying a disulfide group at the N‐terminal, linearly arranged six naphthyl groups at the side chains, and an energy acceptor (anthryl, pyrenyl, or N‐ethylcarbazolyl group) at the C‐terminal were immobilized on a gold surface via a gold‐sulfur linkage to form a well‐defined self‐assembled monolayer with vertical orientation. The monolayer composed of helical peptides terminated with a naphthyl group instead of an energy acceptor was used as control. Upon photoexcitation of the naphthyl groups of the monolayers in solutions containing an electron donor, all the monolayers generated an anodic photocurrent. The photocurrent generation by the monolayers with an acceptor is composed of the following three steps: (1) photon capture by the side‐chain naphthyl groups and energy transfer to the terminal acceptor (light harvesting), (2) electron donation from the aqueous donor to the excited acceptor (electron generation), and (3) electron transport from the terminal to gold via the side‐chain naphthyl groups (electron hopping). Unfortunately, it was found that introduction of an energy acceptor facilitates the light‐harvesting step but suppresses the electron‐generation and electron‐hopping steps, resulting in slight reduction of the efficiency of photocurrent generation compared to the control system. Further detailed discussion on photoenergy and electron transport processes shows a prospect to realize efficient photocurrent generation systems taking advantages of both light harvesting and charge‐transport functions in future. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 1–13, 2013.